Logistics complexity in Indian garment supply chain. (2015) - Rai, Siddharth Shankar; Sharma, Vishal; Ganguly, Kunal
The study focuses on describing the supply chain in a complex environment by taking special reference of the Indian garment industry. It focuses on describing the causes of complexity in the logistics network in order to describe the complexity. Authors differentiate the entire system and its complexity between the logistics complexity and supply chain complexity. After differentiation, the paper focuses on the individual factors of the complexity in both the subsystems and tries to find out the solutions for reducing the complexity.